2016
DOI: 10.1182/blood-2015-12-688747
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil peptides inhibit cleavage of von Willebrand factor by ADAMTS13: a potential link of inflammation to TTP

Abstract: • HNPs inhibit proteolytic cleavage of VWF by ADAMTS13 by physically blocking VWF-ADAMTS13 interactions.• Plasma levels of HNP1, HNP2, and HNP3 are markedly increased in patients with acquired autoimmune TTP.Infection or inflammation may precede and trigger formation of microvascular thrombosis in patients with acquired thrombotic thrombocytopenic purpura (TTP). However, the mechanism underlying this clinical observation is not fully understood.Here, we show that human neutrophil peptides (HNPs) released from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 47 publications
2
67
0
2
Order By: Relevance
“…38 More recently, we demonstrated that HNP1-3 inhibits proteolytic cleavage of VWF by ADAMTS13. 11 Dramatic increases in plasma HNP1-3 are also reported in patients with myocardial infarction, 39,40 systemic lupus erythematosus, 41 and septic meningitis, 42 suggesting that HNP may also play a role in the pathogenesis of other inflammatory and thrombotic disorders. In TTP patients, we speculate that the massive release of HNP1-3 at the sites of vascular W. Cao et al 1324 haematologica | 2016; 101(11) Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 More recently, we demonstrated that HNP1-3 inhibits proteolytic cleavage of VWF by ADAMTS13. 11 Dramatic increases in plasma HNP1-3 are also reported in patients with myocardial infarction, 39,40 systemic lupus erythematosus, 41 and septic meningitis, 42 suggesting that HNP may also play a role in the pathogenesis of other inflammatory and thrombotic disorders. In TTP patients, we speculate that the massive release of HNP1-3 at the sites of vascular W. Cao et al 1324 haematologica | 2016; 101(11) Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our recently published study, wherein we demonstrated that HNP1-3, a group of 29-30 amino acid anti-microbial peptides, potentially released from activated human neutrophils, is a potent inhibitor of ADAMTS13-medidated VWF proteolysis. 11 We hypothesize that the locally released HNP1-3 may play a role in the pathogenesis of acute TTP, particularly in those with severely low circulating ADAMTS13 activity.…”
Section: Human Neutrophil Peptides and Complement Factor Bb In Pathogmentioning
confidence: 97%
“…Additional conditions associated with inflammation can contribute to acute episodes in patients with acquired or hereditary TTP. [14][15][16] The limitations of our analysis are the small number of patients, the small number of relapses that occurred during our follow-up, and that we only measured remission ADAMTS13 activity annually. However, even this small number of patients followed across many years revealed clinically important observations.…”
mentioning
confidence: 99%
“…The present study demonstrates that synthetic HNP‐1 may be a potent inhibitor of platelet adhesion/aggregation onto a fibrillar collagen surface or activated endothelium under arterial flow. These findings were somewhat unexpected because our previous study demonstrated that HNP 1–3 inhibit the proteolytic cleavage of VWF by ADAMTS13 and our initially hypothesis was that the addition of HNP 1–3 to a whole blood containing ADAMTS13 would enhance platelet adhesion/aggregation on a VWF‐collagen surface under arterial shear owing to the expected reduction of VWF proteolysis by ADAMTS13. However, the opposite result was obtained reproducibly.…”
Section: Discussionmentioning
confidence: 80%